Developmental Considerations in Pediatric Skull Base Surgery - LoPresti, Melissa A.; Sellin, Jonathan N.; DeMonte, Franco (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives To review developmental surgical anatomy and technical nuances related to pediatric skull base surgery.Design Retrospective, single-center case series with literature review.Setting MD Anderson Cancer Center.Participants Patients undergoing pediatric skull base surgery.Main Outcome Measures Review developmental anatomy of the pediatric skull base as it relates to technical nuance of various surgical approaches and insight gained from a 25-year institutional experience with this unique patient population.Results Thirty-nine patients meeting these criteria were identified over a 13-year period from 2003 to 2016 and compared to a previously reported earlier cohort from 1992 to 2002. The most common benign pathologies included nerve sheath tumors (11%), juvenile nasopharyngeal angiofibromas (9.5%), and craniopharyngiomas (4.8%). The most common malignancies were chondrosarcoma (11%), chordoma (11%), and rabdomyosarcoma (11%). Varied surgical approaches were utilized and were similar between the two cohorts save for the increased use of endoscopic surgical techniques in the most recent cohort. The most common sites of tumor origin were the infratemporal fossa, sinonasal cavities, clivus, temporal bone, and parasellar region. Gross total resection and postoperative complication rates were similar between the two patient cohorts.Conclusions Pediatric skull base tumors, while rare, often are treated surgically, necessitating an in depth understanding of the anatomy of the developing skull base.
Keywords: pediatric skull base; developmental anatomy; surgery